2009
DOI: 10.1359/jbmr.090522
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Trabecular and Cortical Volumetric BMD in Men of African Ancestry

Abstract: QCT provides a measure of volumetric BMD (vBMD) and distinguishes trabecular from cortical bone. Few studies have determined the factors related to vBMD in men, especially among men of African heritage. This study evaluated the relationship of anthropometric, medical, and behavioral factors and vBMD in a population-based cohort of men of African ancestry (n = 1901) 40 yr of age who had undergone screening for prostate cancer for the first time. Trabecular and cortical vBMD were measured at the radius and tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 66 publications
(103 reference statements)
4
40
1
Order By: Relevance
“…To the best of our knowledge, there is no study about hypertension and HR-pQCT, and there are very few studies about hypertension and QCT [29,30]. For Barbour et al [29], hypertension in men was positively and independently associated with both cortical and trabecular vBMD, whereas no association was found by Sheu et al [30] for men at both distal radius and tibia. Statins are drugs with seemingly multiple actions, for which a possible effect on bone mass has been pointed out.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To the best of our knowledge, there is no study about hypertension and HR-pQCT, and there are very few studies about hypertension and QCT [29,30]. For Barbour et al [29], hypertension in men was positively and independently associated with both cortical and trabecular vBMD, whereas no association was found by Sheu et al [30] for men at both distal radius and tibia. Statins are drugs with seemingly multiple actions, for which a possible effect on bone mass has been pointed out.…”
Section: Discussionmentioning
confidence: 95%
“…When volumetric BMD was assessed by peripheral QCT, cross-sectional data obtained in two studies involving only men found that 'heart disease' (defined by 'myocardial infarction' for the first study and by 'cardiovascular disease' for the second) was not related to trabecular or cortical BMD in either the radius or tibia [29,30]. The most similar study to ours that utilized HR-pQCT compared 66 patients with endstage renal disease on chronic haemodialysis with and without coronary artery calcification (CAC).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies were limited to aBMD but our results are consistent with the results from the Health ABC study, in which men with diabetes had significantly higher lumbar spine trabecular vBMD (25) . Diabetes was also strongly associated with higher trabecular but not cortical vBMD in the peripheral skeleton (27-28) . Since most men in this study had type II diabetes, it is possible that hyperinsulinemia may contribute to greater bone density.…”
Section: Discussionmentioning
confidence: 98%
“…While past smoking was weakly related to lower aBMD of the femoral neck and unrelated to lumbar spine aBMD, smoking had a strong negative impact on trabecular vBMD at both the spine and hip. A study of Afro-Caribbean men also reported a negative association between smoking and trabecular but not cortical vBMD in the peripheral skeleton (36) . The GOOD study also found no association with cortical vBMD (37) .…”
Section: Discussionmentioning
confidence: 98%
“…A total of 1614 men completed the follow-up assessment (80% of survivors). Both the baseline and follow-up visits followed the same procedures for questionnaire interviews, biospecimen collection, and pQCT scans 21 . Hypertension was defined as a systolic blood pressure ≄ 140 mmHg, or a diastolic blood pressure ≄ 90 mmHg, or currently taking anti-hypertensive medications.…”
Section: Methodsmentioning
confidence: 99%